ANALYSIS OF WATER POLLUTION IN VARIOUS TYPES OF MICRO BUSINESS CASE STUDY IN HULUDUOTAMO VILLAGE, SUWAWA DISTRICT, BONE BOLANGO REGENCY - Irwan irwan; Ekawaty Prasetya; Muh rian Tahengo (Universitas Negeri Gorontalo, 2022)
Water pollution is a change in conditions in a water reservoir such as lakes, rivers, oceans and groundwater due to human activities. The purpose of this study was to determine the physical and biological impact of water pollution caused by micro-enterprises in Huluduotamo Village, Suwawa District, Bone Bolango Regency. This type of research is research with a survey approach, namely by making a description or description of a situation objectively. Qualitative research methods are used to solve or answer the problems being faced in the current situation. The results showed that the physical parameters in the Lambongo river were polluted. The results of water quality measurements obtained using physical parameters had exceeded the class (III) water quality standards. Based on biological parameters, well water samples taken in residential areas adjacent to the Lambongo river turned out to be all samples contaminated with Colifrom bacteria and Escherichia Coli bacteria. It is recommended to carry out DLH) Bone Bolango Regency to carry out sanitation inspections especially on Micro-enterprises in Huluduotamo Village Keywords: Water Pollution, Physical Parameters, Biological Parameters.